Global Trends and Conceptual Model of Psychological Determinants of Entrepreneurial Readiness: Bibliometric Analysis and SEM Approach - Andika Sulistiawan; Kamariyah; Wahyu Indah Dewi Aurora; Attiya Istarini; Ali Idrus; Firman; Dwi Noerjoedianto (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2026)
Entrepreneurial readiness is increasingly shaped by psychological factors that enable individuals to adapt and persist in uncertain conditions. Previous, studies on this topic have largely examined psychological factors such as mental health, resilience, and adversity quotient in isolation, resulting in a fragmented understanding of their combined influence on entrepreneurial outcomes.Therefore this study aims to address the stated gap by integrating the outlined constructs within a unified framework. In order to achieve this objective, a sequential mixed-method design was adopted, combining bibliometric analysis of 356 Scopus-indexed documents (2010–2025) with Structural Equation Modeling (PLS-SEM) based on data from 412 health students. The bibliometric findings identified resilience, adversity quotient, and mental well-being as growing themes in entrepreneurship exploration. SEM results showed that adversity quotient had the strongest effect on entrepreneurial readiness (β=.734, p<.001), followed by resilience (β=.466, p<.001) and mental health (β=.260, p=.046). Resilience also significantly mediated these relationships. TCollectively, these findings suggest that resilience, adversity quotient, and mental health are foundational components of entrepreneurial readiness and should be integrated into entrepreneurship education and student development programs.